2014
DOI: 10.3813/aaa.918726
|View full text |Cite
|
Sign up to set email alerts
|

Birdsong As an Element of the Urban Sound Environment: A Case Study Concerning the Area of Warnemünde in Germany

Abstract: SummaryBirds are common species in urban ecosystems and birdsong is an important element of many urban sound environments. Perceptions of birdsong loudness, based on a case study in Warnemünde, a coastal area in Germany, were analysed in terms of its role in urban sound environment, the relationships with other sounds, spatiotemporal characteristics, as well as the relationships with underlying landscape characteristics. An important and positive role of birdsong in urban soundscape perception in the study are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 37 publications
0
13
1
Order By: Relevance
“…For instance, attempts have been made to map directly some soundscape dimensions (e.g. 'calmness', like in Figure 6), starting from individual data collected on site through soundwalks (e.g., Liu, Kang, Luo, Behm, & Coppack, 2013;Liu, Kang, & Behm, 2014;Aletta, Margaritis, Filipan, Puyana Romero, Axelsson, & Kang, 2015;Aiello, Schifanella, Quercia, & Aletta, 2016). The hypothesis for developing such maps is that based on the soundscape information on certain locations in an area, the soundscape of the whole area could be predicted with spatial interpolation analysis method in GIS platforms.…”
Section: How Can We 'Represent' Soundscapes?mentioning
confidence: 99%
“…For instance, attempts have been made to map directly some soundscape dimensions (e.g. 'calmness', like in Figure 6), starting from individual data collected on site through soundwalks (e.g., Liu, Kang, Luo, Behm, & Coppack, 2013;Liu, Kang, & Behm, 2014;Aletta, Margaritis, Filipan, Puyana Romero, Axelsson, & Kang, 2015;Aiello, Schifanella, Quercia, & Aletta, 2016). The hypothesis for developing such maps is that based on the soundscape information on certain locations in an area, the soundscape of the whole area could be predicted with spatial interpolation analysis method in GIS platforms.…”
Section: How Can We 'Represent' Soundscapes?mentioning
confidence: 99%
“…Soundscape studies [22,30] suggested that people usually favornature sounds such as water sound and birdsong. In this study,three kinds of water sounds (WS1, WS2 and WS3)w ere added to original noise samples separately.…”
Section: Subjective Annoyance Evaluation Resultsmentioning
confidence: 99%
“…Soundscape studies [31] suggested that ac omfortable acoustic environment largely depends on sound source type; some pleasant sounds, even though their SPLs are higher,may create more comfortable atmosphere. One of the common proposed solutions to improve the soundscape in urban spaces is to introduce natural sounds to mask urban noises such as road traffica nd construction noises [30]. Jeon et al [15] studied the soundscape of urban spaces and found that introducing water sound could improve the subjective perception of urban spaces soundscape.…”
Section: Effects Of Sace Valuated By Subjective Evaluation Testmentioning
confidence: 99%
“…It is noteworthy that these birds are better perceived in the center of the garden than at its periphery [32]. The data layer "gardens" of the IGN's¹ BD TOPO French database was used.…”
Section: Density Of Gardensmentioning
confidence: 99%